Annihilation of the triplet excitons in the nanoporous glass matrices - Afanasyev, D.A.; Ibrayev, N.Kh.; Saletsky, A.M.; Starokurov, Y.V.; Gun'ko, V.M.; Mikhalovsky, S.V. (Journal of Luminescence, 2013)
Abstract The spectra and kinetics of fluorescence decay of 1,2-benzanthracene (1,2-BA) molecular clusters adsorbed in nanoporous borosilicate glasses were investigated. It has been shown that the type of the decay kinetics of delayed fluorescence is determined by the annihilation of triplet excitons in crystalline and percolation clusters. The influence of an external magnetic field on the annihilation rate constant of triplet excitons in the adsorbed 1,2-BA molecules has been studied. The response of the molecular clusters to the magnetic field strongly depends on temperature, pore size and time scale of the observation. Clusters with the crystal structure dominate in the decay kinetics of triplet–triplet annihilation (TTA) and delayed fluorescence in the initial microsecond period of time after excitation. Amorphous clusters determine the form of decay kinetics of delayed fluorescence in the millisecond range. The increase in the pore size and concentration of the adsorbate lead to the dominance of crystalline components. The results presented here can be used to develop techniques for probing the structure of the adsorbed layer in nanoporous systems examining the effect of an external magnetic field on the annihilation delayed fluorescence (ADF) kinetics.
Keywords: Delayed fluorescence; Triplet–triplet annihilation; Magnetic field effect; Porous glasses; Molecular clusters